2015
DOI: 10.13076/tjo-d-15-00010
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implant Usage in Orthodontic Practice

Abstract: Ates x; 3 and Nazan Kü çü kkeles x 4 ABSTRACT Objective: The present study was designed to investigate the general anchorage protocols and especially the tendencies during mini-implant usage among Turkish orthodontists. The main aim of the survey is to reveal if mini-implants are being used more than once and in different patients. Materials and Method: This is a cross-sectional study conducted with orthodontists who are members of the Turkish Orthodontic Society. The orthodontists were asked to click on a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…TiO 2 is chemically stable and inert and is ideal for insertion into bone [ 13 ]. TiO 2 has photo-catalytic properties (in its anatase form) that prevent the colonization of pathogenic microorganisms [ 27 ]. This TiO 2 layer, also called the passivation layer, exists in all TADs tested in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 is chemically stable and inert and is ideal for insertion into bone [ 13 ]. TiO 2 has photo-catalytic properties (in its anatase form) that prevent the colonization of pathogenic microorganisms [ 27 ]. This TiO 2 layer, also called the passivation layer, exists in all TADs tested in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…These changes occur because the concentration of chloride ions in the interstitial fluid, as well as the salivary assortment of amino acids and proteins, produces a corrosive environment for metallic materials. The dietary intake of a particular element may vary as a result of individual consumption, as well as geographical location, but studies have shown that the amount of vanadium released from Ti alloy in TADs is well below the daily alimentary intake of this element [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey carried out in Turkey in 2014, 41% of participants replied that they were using miniscrews more than once (13). Although the recycling and reuse of invasive materials may create an ethical concern and should not be encouraged, re-insertion of a miniscrew can be considered in the same patient (especially in cases of early failure, they can be re-inserted in a different location), if sterilization and previous insertion processes do not create any alteration in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Even in some cases requiring surgery, camouflage treatment becomes possible without surgery using skeletal anchorage (11). Intrusion, extrusion, impacted tooth movement, space closing, and tooth uprighting can be achieved using miniscrews (12).…”
Section: Introductionmentioning
confidence: 99%